2018
DOI: 10.1096/fj.201700665r
|View full text |Cite
|
Sign up to set email alerts
|

Fibromodulin and regulation of the intricate balance between myoblast differentiation to myocytes or adipocyte‐like cells

Abstract: Interactions between myoblasts and the surrounding microenvironment led us to explore the role of fibromodulin (FMOD), an extracellular matrix protein, in the maintenance of myoblast stemness and function. Microarray analysis of FMOD kd myoblasts and in silico studies were used to identify the top most differentially expressed genes in FMOD kd , and helped establish that FMOD-based regulations of integral membrane protein 2a and clusterin are essential components of the myogenic program. Studies in knockout, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…Microarray analysis was conducted with the Agilent Technologies mouse GE4X 44K (V2) chip to determine the differentially expressed genes in wild-type (TTR wt ) and TTR kd (TTR knockdown) cells as described previously [30]. Briefly, TTR wt and TTR kd cells were grown in serum (+) differentiation media for two days and RNAs were extracted, synthesized into cDNA with fluorescence using a Low RNA Input Linear Amplification kit (Agilent Technologies, CA, USA) according to the manufacturer's instructions.…”
Section: Microarray Analysismentioning
confidence: 99%
“…Microarray analysis was conducted with the Agilent Technologies mouse GE4X 44K (V2) chip to determine the differentially expressed genes in wild-type (TTR wt ) and TTR kd (TTR knockdown) cells as described previously [30]. Briefly, TTR wt and TTR kd cells were grown in serum (+) differentiation media for two days and RNAs were extracted, synthesized into cDNA with fluorescence using a Low RNA Input Linear Amplification kit (Agilent Technologies, CA, USA) according to the manufacturer's instructions.…”
Section: Microarray Analysismentioning
confidence: 99%
“…Furthermore, two major SM ECM proteins, that is, collagen and laminin, are known to be associated with myopathies. In previous studies, we explored the roles of a small number of ECM proteins like fibromodulin, matrix gla proteins, and dermatopontin during different stages of myogenesis (Lee et al, 2016;Ahmad et al, 2017;Lee et al, 2018;Kim et al, 2019) and found fibromodulin, as well as dermatopontin, is involved in the vigorous recruitment of MSCs at sites of injury, and thus, aids SM regeneration Kim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing studies have suggested FMOD as a crucial regulator of wound healing [ 12 , 17 , 25 28 ], which leads to the speculation that FMOD may also play a special role in the pathological progression of PVR, the process of wound healing in the eye. It is known that RPE plays critical roles in eye fibrosis, which raises the question that whether FMOD is associated with the abnormal activation of RPE.…”
Section: Discussionmentioning
confidence: 99%